Identification of a novel splice variant of human PD-L1 mRNA encoding an isoform-lacking Igv-like domain - HE Xian-hui; XU Li-hui; LIU Yi (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the expression and regulation of PD-1 ligand 1 (PD-L1) in peripheral blood mononuclear cells (PBMC). Methods: The cDNA encoding human PD-L1 precursor was cloned from the total RNA extracted from the resting and phorbol dibutyrate plus ionomycin- or phytohemagglutinin-activated PBMC, by reverse transcription polymerase chain reaction (RT-PCR), and independent clones were sequenced and analyzed. The expression and subcellular localization were examined in transiently transfected cells. The PD-L1 gene expression in different PBMC was also analyzed by RT-PCR. Results: A novel human PD-L1 splice variant was identified from the activated PBMC. It was generated by splicing out exon 2 encoding an immunoglobulin variable domain (Igv)-like domain but retaining all other exons without a frame-shift. Consequently, the putative translated protein contained all other domains including the transmembrane region except for the Igv-like domain. Furthermore, the conventional isoform was expressed on the plasma surface whereas the novel isoform showed a pattern of intracellular membrane distribution in transiently transfected K562 cells. In addition, the expression pattern of the PD-L1 splice variant was variable in different individuals and in different cellular status. Conclusion: PD-L1 expression may be regulated at the posttranscriptional level through alternative splicing, and modulation of the PD-L1 isoform expression may influence the outcome of specific immune responses in the peripheral tissues.